1986
DOI: 10.1007/bf00316320
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation pharmacokinetics of 1,2-dichloroethane after different dietary pretreatments of male Sprague-Dawley rats

Abstract: The effect of the pretreatment of male Sprague-Dawley rats with phenobarbital (PB), butylated hydroxyanisole (BHA) and disulfiram (DSF) on the inhalation kinetics of 1,2-dichloroethane [ethylene dichloride (EDC)] was studied by the gas uptake method. A closed recirculating system was constructed and characterized. The rate curves in all the pretreatment regimens showed saturable dependence on EDC concentration. These saturable dependencies (Michaelis-Menten) appeared to be associated with enzymatic metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The metabolic intermediates produced in CYP2E1 mediated 1,2-DCE metabolism are 2-chloroethanol (2-CE) and chloroacetaldehyde, which are proposed to be involved in the toxic effects induced by 1,2-DCE poisoning, because they are more reactive than 1,2-DCE itself (Guengerich et al, 1980; Igwe et al, 1986; Raucy et al, 1993). Therefore, it is indispensable for exploring the neurotoxicity directly caused by 2-CE.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic intermediates produced in CYP2E1 mediated 1,2-DCE metabolism are 2-chloroethanol (2-CE) and chloroacetaldehyde, which are proposed to be involved in the toxic effects induced by 1,2-DCE poisoning, because they are more reactive than 1,2-DCE itself (Guengerich et al, 1980; Igwe et al, 1986; Raucy et al, 1993). Therefore, it is indispensable for exploring the neurotoxicity directly caused by 2-CE.…”
Section: Introductionmentioning
confidence: 99%
“…Although its expression in the brain is much lower than in the liver, the enzyme is highly concentrated and inducible in the cortical astrocytes [34][35][36][37]. It has been reported that CYP2E1 can convert 1,2-DCE into 2-CE, chloroacetaldehyde and chloroacetic acid [38][39][40][41]. Because of the high oxidase activity, CYP2E1-mediated metabolism of 1,2-DCE and its intermediates can lead to the generation of ROS, as a consequence induce oxidative damage in the brain [20,33] The present results revealed that CYP2E1 knockdown reversed 2-CE-induced augmentation of ROS production and A1s induction, suggesting that ROS production is involved in A1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 2-chloroethanol (2-CE), a metabolite of 1,2-DCE generated in vivo via microsomal CYP2E1, is more reactive than its parent molecule, and therefore might play an important role in the toxic effects of 1,2-DCE [ 4 , 5 , 6 ]. Our studies showed that matrix metalloproteinases-9 (MMP-9) was transcriptionally upregulated in 2-CE-treated astrocytes in vitro [ 7 ], as well as in the early phase of brain edema induced by subacute 1,2-DCE poisoning in mice [ 8 ].…”
Section: Introductionmentioning
confidence: 99%